Subcritical water extraction of Chlorella pyrenoidosa: optimization through response surface methodology - Thiruvenkadam, Selvakumar; Siajam, Shamsul Izhar; Hiroyuki, Yoshida; Harun, Mohd Razif (Hindawi, 2018)
Subcritical water extraction (SCW) was used to extract oil from Chlorella pyrenoidosa. The operational factors such as reaction temperature, reaction time, and biomass loading influence the oil yield during the extraction process. In this study, response surface methodology was employed to identify the desired extraction conditions for maximum oil yield. Experiments were carried out in batch reactors as per central composite design with three independent factors including reaction temperature (170, 220, 270, 320, and 370°C), reaction time (1, 5, 10, 15, and 20 min), and biomass loading (1, 3, 5, 10, and 15%). A maximum oil yield of 12.89 wt.% was obtained at 320°C and 15 min, with 3% biomass loading. Sequential model tests showed the good fit of experimental data to the second-order quadratic model. This study opens the great potential of SCW to extract algal oil for use in algal biofuel production.